The evolution, progress, and future direction of Nepal's universal salt iodization program. (3rd February 2020) - Paudyal, Naveen; Chitekwe, Stanley; Rijal, Sanjay; Parajuli, Kedar; Pandav, Chandrakant; Maharjan, Macha; Houston, Robin; Gorstein, Jonathan
Abstract: Nepal is located in what was once known as the Himalayan Goitre Belt and once had one of the highest prevalence's of iodine deficiency disorders in the world. However, through a well‐executed universal salt iodization program implemented over the past 25 years, it has achieved optimal iodine intake for its population, effectively eliminating the adverse consequences of iodine deficiency disorders. A comprehensive review of policy and legislation, surveys, and program reports was undertaken to examine the key elements contributing to the success of this program. The paper reviews the origins and maturation of salt iodization in Nepal, as well as trends in the coverage of iodized salt, the iodine content in salt, and population iodine status over the past two decades. The paper describes critical components of the program including advocacy efforts, trade issues with India, the role of the Salt Trading Corporation, monitoring, and periodic program reviews. The paper discusses the recent findings from the 2016 national micronutrient survey demonstrating the success of the salt iodization program and describes emerging challenges facing the program in the future.